2010
DOI: 10.1200/jco.2009.27.6899
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IDH1 R132 Mutations and an IDH1 Single Nucleotide Polymorphism in Cytogenetically Normal Acute Myeloid Leukemia: SNP rs11554137 Is an Adverse Prognostic Factor

Abstract: IDH1 SNP rs11554137 but not IDH1 R132 mutations are associated with an inferior outcome in CN-AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
229
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(264 citation statements)
references
References 27 publications
31
229
2
2
Order By: Relevance
“…20,24 Genomic and mitochondrial DNA were extracted from samples using the All Prep DNA/RNA Kit (Qiagen, Hilden, Germany) according to the manufacturer's recommendations. Complete coverage of the mitochondrial ND4 gene sequence was accomplished using three overlapping PCR.…”
Section: Analysis Of Nd4 Mutationsmentioning
confidence: 99%
“…20,24 Genomic and mitochondrial DNA were extracted from samples using the All Prep DNA/RNA Kit (Qiagen, Hilden, Germany) according to the manufacturer's recommendations. Complete coverage of the mitochondrial ND4 gene sequence was accomplished using three overlapping PCR.…”
Section: Analysis Of Nd4 Mutationsmentioning
confidence: 99%
“…1 We recently investigated hematopoiesis in Wnt3a-deficient mice. 2 Due to early embryonic lethality, 3 this analysis was performed in fetal liver (FL) at embryonic day 12.5. Remarkably, Wnt3a deficiency leads to reduced numbers of long-term HSC and multipotent progenitors, which are severely and irreversibly impaired in long-term reconstitution capacity as observed in serial transplantation assays.…”
Section: Wnt3a Nonredundantly Controls Hematopoietic Stem Cell Functimentioning
confidence: 99%
“…1 Very recently, a series of reports about this mutation in AML have been published in a cluster of manuscripts. [1][2][3][4][5][6][7] As IDH1 mutation brings prognostic information in glioma and possibly AML, 4,[8][9] identification of IDH1 R132 mutations will bring increasing clinical relevance. Moreover, the mutation seems quite stable and may serve as a marker for monitoring minimal residual disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first reports came from studies in AML. Initially uncovered by a whole-genome sequencing survey, 21 the IDH1 R132C mutation was subsequently searched in large cohorts of primary AML cases 1,[21][22][23][24][25][26][27] and was found to be detectable in a proportion of patients varying from 4.4 to 14%. Some of these studies also identified mutations affecting IDH2 R172 in 1.1-3.6% of cases, and a novel R140Q mutation in 6-15.6% of cases.…”
mentioning
confidence: 99%